Effect of ezetimibe–statin combination therapy vs. statin monotherapy on coronary atheroma phenotype and lumen stenosis in patients with coronary artery disease: a meta-analysis and trial sequential analysis - Zhang, Yun-Jing; Xu, Min; Duan, Ji-Qiang; Wang, De-Jin; Han, Shi-Liang (Frontiers in Pharmacology, 2024)
Background: Evidence indicates that the addition of ezetimibe to statin therapy reduces cardiovascular events. However, the impact of ezetimibe-statin combination therapy on coronary plaque regression, plaque stabilization, diameter stenosis remains a matter of controversy. Methods: We performed electronic searches in Pubmed, Web of Knowledge, Cochrane Central Register of Controlled Trials to identify eligible trials assessing the effects of ezetimibe-statin combination therapy versus statin monotherapy reporting at least one outcome among total atheroma volume (TAV), minimum fibrous cap thickness (FCT), lumen volume (LV) and lumen area (LA) derived from intravascular imaging modalities of intravascular ultrasound (IVUS) and Optical coherence tomography (OCT). We used the random-effects model and performed trial sequential analysis (TSA) during this meta-analysis. Results: 11 articles with a total of 926 individuals (460 in the dual lipid-lowering therapy group and 466 in the statin monotherapy group) were included in the final meta-analysis. Compared to statin monotherapy, ezetimibe-statin combination therapy was associated with significant decreased TAV [WMD = -3.17, 95% CI (-5.42 to -0.92), and P=0.006], with no effect on LV of coronary artery [WMD = -0.52, 95% CI (-2.24 to 1.21), and P=0.56], LA of coronary artery [WMD =0.16, 95% CI ( -0.10 to 0.42), and P=0.22] and minimum FCT thickness [WMD = 19.11, 95%CI ( -12.76 to 50.97)]. Conclusion: In patients with coronary artery disease, ezetimibe-statin combination therapy resulted in a significant regression in TAV compared to statin monotherapy, whereas no overall improvement of minimum FCT and lumenal stenosis was observed.